Formation of Self-Assembled Liquid Crystalline Nanoparticles and Absorption Enhancement of Ω-3s by Phospholipids and Oleic Acids - Sang-Won Jeon; Han-Sol Jin; Young-Joon Park (MDPI AG, 2021)
This study aimed to optimize and evaluate self-assembled liquid crystalline nanoparticles (SALCs) prepared from phospholipids and oleic acid for enhancing the absorption of Ω-3s. We explored the structure and optimal formulation of SALCs, which are composed of Ω-3 ethyl ester (Ω-3 EE), phospholipids, and oleic acid, using a ternary diagram and evaluated the improvement in Ω-3 dissolution, permeation, and oral bioavailability. The in vitro dissolution and pharmacokinetics of Ω-3 SALCs were compared with those of Omacor soft capsules (as the reference). The shape of the liquid crystal was determined according to the composition of phospholipids, oleic acids, and Ω-3s and was found to be in cubic, lamellar, and hexagonal forms. The dissolution rates of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) obtained from Ω-3 SALCs were 1.7 to 2.3-fold higher than those of the Omacor soft capsules. Furthermore, a pharmacokinetic study in male beagle dogs revealed that Ω-3 SALCs increased the oral bioavailability of Ω-3 EE by 2.5-fold for EPA and 3.1-fold for DHA compared with the reference. We found an optimal formulation that spontaneously forms liquid crystal-based nanoparticles, improving the bioavailability of EPA and DHA, not found in the existing literature. Our findings offer insight into the impact of nanoparticle phase on the oral delivery of oil-soluble drugs and provide a novel Ω-3 EE formulation that improves the bioavailability of EPA and DHA.